Pneumococci Can Become Virulent by Acquiring a New Capsule From Oral Streptococci. (7th September 2019) - Nahm, Moon H; Brissac, Terry; Kilian, Mogens; Vlach, Jiri; Orihuela, Carlos J; Saad, Jamil S; Ganaie, Feroze
Abstract: Pneumococcal conjugate vaccines have been successful, but their use has increased infections by nonvaccine serotypes. Oral streptococci often harbor capsular polysaccharide (PS) synthesis loci ( cps ). Although this has not been observed in nature, if pneumococcus can replace its cps with oral streptococcal cps, it may increase its serotype repertoire. In the current study, we showed that oral Streptococcus strain SK95 and pneumococcal strain D39 both produce structurally identical capsular PS, and their genetic backgrounds influence the amount of capsule production and shielding from nonspecific killing. SK95 is avirulent in a well-established in vivo mouse model. When acapsular pneumococcus was transformed with SK95 cps, the transformant became virulent and killed all mice. Thus, cps from oral Streptococcus strains can make acapsular pneumococcus virulent, and interspecies cps transfer should be considered a potential mechanism of serotype replacement. Our findings, along with publications from the US Centers for Disease Control and Prevention, highlight potential limitations of the 2013 World Health Organization criterion for studying pneumococcal serotypes carried without isolating bacteria. We show that an oral streptococcal strain, SK95, and a pneumococcal strain, D39, both produce chemically identical capsular PS. We also show that transferring SK95 cps into noncapsulated, avirulent pneumococcus gave it the capacity for virulence in a mouse model.